LEGAL REVIEW OF THE GRANTING OF MARRIAGE DISPENSATION BY THE COURT FOR UNDERAGE CHILD MARRIAGE BASED ON LAW NO. 16 OF 2019 AS AN AMENDMENT TO LAW NO. 1 OF 1974 CONCERNING MARRIAGE - Maharani, Maharani; Henry Aspan; Azhali Siregar (International Journal of Synergy in Law, Criminal, and Justice, 2025)
Child marriage is a phenomenon that still occurs in Indonesia even though the government has taken various steps to prevent it, one of which is through the revision of Law Number 1 of 1974 to Law Number 16 of 2019 concerning Marriage. In this regulation, the minimum age limit for marriage is raised to 19 years for men and women. However, this regulation still provides room for child marriage through the marriage dispensation mechanism, as regulated in Article 7 paragraph (2). This dispensation allows parents to submit an application to the religious court on urgent grounds. Ironically, in practice, the courts tend to grant almost all requests for marriage dispensation, which is contrary to the original purpose of the law to reduce the number of child marriages. This study aims to analyze the effectiveness of granting marriage dispensation from a legal perspective and its impact on the protection of minors. The research method used is a normative legal approach by analyzing related regulations, legal doctrines, and court decisions. The results of the study indicate that the marriage dispensation mechanism is still a legal loophole that allows the practice of child marriage to continue to occur. The main factors influencing the high number of marriage dispensations include social pressure, economic factors, and cultural norms that still consider early marriage as a solution to various family problems. Therefore, efforts are needed to tighten regulations, increase public legal awareness, and strengthen the role of child protection institutions so that marriage dispensation is not misused and truly functions as a child protection mechanism in accordance with the principle of legal benefit.